Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/9048324
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Submerged Arc Welding Process Parameters on the Mechanical Properties of Pressure Vessel Steel ASTM A283 Grade A

Abstract: The pressure vessel steel is used in boilers and pressure vessel structure applications. This research studied the effects of submerged arc welding (SAW) process parameters on the mechanical properties of this steel. The weld sample originated from ASTM A283 grade A sheet of 6.00-millimeter thickness. The welding sample was treated using SAW with the variation of three process factors. For the first factor, welding currents of 260, 270, and 280 amperes were investigated. The second factor assessed the travel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These results revealed that friction welding below the temperature can improve the mechanical properties of similar joints of medium and Carbon steel. Peasura (2017) studied the effects of submerged arc welding (SAW) process parameters on the mechanical properties of pressure vessel ASTM A283 steel. The weld samples were obtained from an ASTM A283 grade sheet of 6.00 mm thickness.…”
Section: Electric Arc Welding Processesmentioning
confidence: 99%
“…These results revealed that friction welding below the temperature can improve the mechanical properties of similar joints of medium and Carbon steel. Peasura (2017) studied the effects of submerged arc welding (SAW) process parameters on the mechanical properties of pressure vessel ASTM A283 steel. The weld samples were obtained from an ASTM A283 grade sheet of 6.00 mm thickness.…”
Section: Electric Arc Welding Processesmentioning
confidence: 99%
“…Welding parameters such as current, voltage and travel speed are the principal parameters of submerged arc welding (SAW). Increasing the welding current to improve deposition rate, leads to an increase in heat input [8,9]. In addition, this leads to deeper penetration and higher melting rate of welding wire.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure vessels can be used in harsh environments with high temperatures and pressures, as well as extremely low temperatures [ 18 ]. Thus, high-quality properties of thick plates are required, including a good combination of strength and toughness; as a result, the quality of welding joints must be improved [ 19 , 20 ]. Moreover, for high tensile strength, the carbon content of the weld metal should be increased [ 21 ].…”
Section: Introductionmentioning
confidence: 99%